A carnival of snackery [compact disc, unabridged] : diaries (2003-2020) - Sedaris, David (Hachette Audio, 2021)
In this follow-up to his previous volume of diaries, Theft by Finding, the award-winning humorist chronicles the years 2003-2020, charting the years of his rise to fame with his trademark misanthropic charm and wry wit.